Quiltra subjectivities: Interview with María del Carmen Pérez Cuadra - Grivell, Lynette (2025)
This interview emerged from Lynette Grivell’s PhD study at the University of New England, Australia, about Fantastic stories written by a selection of women authors from Mexico, Central America, and the Caribbean. One of the texts analysed is ‘Muñeca Rota’ by María del Carmen Pérez Cuadra, included in her book Una ciudad de estatuas y perros (2022). The interviewers’ aim was to find out what were the themes of the book, the themes or sub-themes in ‘Muñeca Rota’ and the reason for the choice of the dolls, how this story relates to the other stories in the book, and any relationship between this book and her other novels. In addition, the recent boom in Latin American women’s writing was discussed, as well as Pérez Cuadra’s relationship with these writers and whether Central American women writers have joined this boom. Access to publishers for Central American writers was highlighted as an issue of concern.